2004
DOI: 10.3201/eid1009.030745
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Botulism in the United States, 1990–2000

Abstract: Home-canned foods and Alaska Native foods are leading causes of U.S. foodborne botulism; botulism’s epidemic potential renders each case a public health emergency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 15 publications
1
137
0
11
Order By: Relevance
“…Type E botulism is endemic in Alaska and northern Canada, where the annual incidence ranges from 6.9 to 50.5 cases per 100,000 population [1,2]. The Canadian Inuit population has been primarily exposed to botulinum neurotoxin type E via the consumption of aged marine mammal products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Type E botulism is endemic in Alaska and northern Canada, where the annual incidence ranges from 6.9 to 50.5 cases per 100,000 population [1,2]. The Canadian Inuit population has been primarily exposed to botulinum neurotoxin type E via the consumption of aged marine mammal products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…C. botulinum is commonly found in the soil, and its spores have been found on raw potatoes (5). Several outbreaks of botulism caused by eating potatoes have occurred in the United States (6)(7)(8), and laboratory studies have shown that C. botulinum spores on the surface of raw potatoes can survive baking and lead to production of botulinum toxin (5). The warm anaerobic fermentation process of making pruno probably predisposes toward production of botulinum toxin, particularly if any ingredient happens to be contaminated with C. botulinum or its spores, such as the potatoes used in these 2 instances.…”
Section: Discussionmentioning
confidence: 99%
“…Food items involved in these cases were home-canned, including soups, tomato sauce, garlic in oil, stew, potato salad, homemade sausages and, less frequently, meatballs, steak, liver pâté, bread pudding, apple pie sauce, hamburger, chili and peyote [4]. Also, in the United States, there have been outbreaks caused by food prepared in restaurants, such as the sauce, skordalia, made from potatoes and cheese.…”
Section: Epidemiology Of Botulism Outbreaksmentioning
confidence: 99%
“…However, home-canned foods represented the main cause for botulism, not only of sporadic cases but also in the outbreaks reported from restaurant food [4]. Traditional food from Alaska, especially fish, fish eggs, seals, beavers and whales, which are processed by allowing room temperature fermentation and then consumed without cooking [5], are sources of botulism in that geographic area.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%